Protest Policing, Normative Alignment, and Riot Gear: An Experiment - Thompson, Andrew J. (Crime & delinquency, 2025)
To examine if police expressions of solidary with protesters improve public opinion toward the police, we embedded a picture- and information-based experiment in a YouGov survey (N = 1,150), wherein respondents were randomly exposed to police expressions of solidarity with protesters. We also randomized whether the pictured officers were wearing riot gear. We find little evidence that expressions of solidarity or riot gear significantly affect public affinity for the police or support for accountability reforms in policing. Past studies show that outside of the context of protests, officers’ behavior toward civilians has asymmetric effects, such that positive actions matter less than negative ones. Our findings suggest that this may be true within the protest context as well.